If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2z+5(z-1)=3z-1
We move all terms to the left:
2z+5(z-1)-(3z-1)=0
We multiply parentheses
2z+5z-(3z-1)-5=0
We get rid of parentheses
2z+5z-3z+1-5=0
We add all the numbers together, and all the variables
4z-4=0
We move all terms containing z to the left, all other terms to the right
4z=4
z=4/4
z=1
| 16x-13x-2x+2=7 | | 1/2(4x+8)=-1/2(-6x-12) | | 3a+1=-3.6(a-10) | | 6p–4+12p=-20+16p | | 15=13-x | | 2+2x=6x-2 | | 2.27x-0.27x+0.6=11.0 | | x2+2x+5=0 | | 6+2(3j-2)=4(1+j | | 5f-41=3f-9 | | .05X+.1X+.25x=2 | | -3n+-4n-5=0 | | 4x²+6x=0 | | 5x-15=20- | | .5X+.1X+.25x=2 | | 2y^2+3y=27 | | −2(7+2k)=3k | | -5m=100 | | -15n*18n+-4n-5=0 | | 2x^2+17x=-8 | | 3/2(9x-6)=8 | | 10-m=-30 | | X(2x-5)=(2x+5)(x-4) | | 3x-10=5(x+2)-2x | | -0.8x=64 | | 4/2x-1=3/11 | | 5(4+2x)=0 | | 8-3(-12x+2)=0 | | 8=2/3(9x-6) | | 14u-13u-1=17 | | 2.6v=7.5 | | 10x-2x-9=-45+12x |